Answer:
Step-by-step explanation:
The system of equations given are:
5x - y + z = -6 ------------- i
2x + 7y + 3z = 8 ---------- ii
x + 2z = 6 ----------------- iii
Let us deal with equation i and ii first since they have 3 variables x, y and z;
5x - y + z = -6 x 7
2x + 7y + 3z = 8 x 1
35x - 7y + 7z = -42 ---- iv
2x + 7y + 3z = 8 ---- v
Add equation iv and v;
37x + 10z = -34 ------vi
So, let us solve equation vi and iii:
x + 2z = 6 - ---------- iii x 10
37x + 10z = -34 --- iv x 2
10x + 20z = 60 vi
74x + 20z = -68 vii
Subtract vi - vii;
-64x = 128
x = -2
So; put x = -2 into iii;
x + 2z = 6
-2 + 2z = 6
2z = 6 + 2 = 8
z = 4
Put x = -2 and z = 4 into equation i;
5(-2) - y + 4 = - 6
-10 -y +4 = -6
-6 - y = -6
-y = 0
y = 0
I think the answer is 5x + 6y + 1
Answer: hello your question is poorly written attached below is the complete question
answer:
--- ( option d )
Step-by-step explanation:
The correct option that represents a square root of 3 as related to the question attached below is :
![\sqrt{3}(cos(\frac{3\pi }{2}) + isin(\frac{3\pi }{2}))](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D%28cos%28%5Cfrac%7B3%5Cpi%20%7D%7B2%7D%29%20%2B%20isin%28%5Cfrac%7B3%5Cpi%20%7D%7B2%7D%29%29)
Answer:
I think it’s 105
Step by step explanation:
I hope this helped in some kind of way.
Answer: 29/4
Step-by-step explanation: